(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Khushwant Singh’s chosen novels provide insight into the socio-cultural landscape of India. Therefore, adopting a pragmatic approach becomes essential to effectively explore the language employed by the author. This approach proves invaluable in not only revealing the distressing circumstances faced by marginalized segments of Indian society but also in unraveling the attitudes of the high caste/class individuals through the linguistic behaviors of the characters.